Emotional education program to improve the level of self-esteem of the students of the 2nd. Grade of Primary Education of I.E. 80822 "Santa María of the Esperanza" (SCIÉNDO INGENIUM, 2022)
The purpose of the research was to determine the influence of the application of the emotional education program on the improvement of self-esteem levels in children of the second grade of primary education of the I.E. Nº 80822 “Santa María de la Esperanza”, Trujillo in 2019. It was Quasi-experimental type investigation, a Pretest and Post-Test design was used with an experimental group and a control group, the sample was of 30 students, The instrument used to The data collection of our research work was: Self-esteem Test - 25, for the hypothesis test, the Student's t test was used to compare means of self-esteem in the experimental and control groups; The results showed that the application of the program managed to significantly improve self-esteem in the children of the study sample, through the permanent learning and practice of positive emotions such as developing the ability to love oneself and others, practicing and promoting practice in others of laughter, joy and happiness, value themselves and learn to value others, practice acts of courage and security.
Keywords: self-esteem; emotional education; positive emotions